Phosphine Oxide Porous Organic Polymers Incorporating Cobalt(II) Ions: Synthesis, Characterization, and Investigation of H2 Production - Bonfant, Giulia; Balestri, Davide; Perego, Jacopo; Comotti, Angiolina; Bracco, Silvia; Koepf, Matthieu; Gennari, Marcello; Marchiò, Luciano (ACS omega, 2022)
Suitably functionalized porous matrices represent versatile platforms to support well-dispersed catalytic centers. In the present study, porous organic polymers (POPs) containing phosphine oxide groups were fabricated to bind transition metals and to be investigated for potential electrocatalytic applications. Cross-linking of mono- and di-phosphine monomers with multiple phenyl substituents was subject to the Friedel–Crafts (F-C) reaction and the oxidation process, which generated phosphine oxide porous polymers with pore capacity up to 0.92 cm3/g and a surface area of about 990 m2/g. The formation of the R3P·BH3 borohydride adduct during synthesis allows to extend the library of phosphine-based monomeric entities when using FeCl3. The porous polymers were loaded with 0.8–4.2 w/w % of cobalt(II) and behaved as hydrogen evolution reaction (HER) catalysts with a Faradaic efficiency of up to 95% (5.81 × 10–5 mol H2 per 11.76 C) and a stable current density during repeated controlled potential experiments (CPE), even though with high overpotentials (0.53–0.68 V to reach a current density of 1 mA·cm–2). These studies open the way to the effectiveness of tailored phosphine oxide POPs produced through an inexpensive and ecofriendly iron-based catalyst and for the insertion of transition metals in a porous architecture, enabling electrochemically driven activation of small molecules.